Brachial plexus and nerves of upper limb - Banumathy, S. P. (Henry Stewart Talks, 2022)
Brachial plexus, Upper plexus injury, Lower plexus injury, Nerves of the upper limb, Median nerve, Ulnar nerve, Radial nerve, Axillary nerve, Musculocutaneous nerve